Known and unknown high mathematics conspectus of the end of the 4th decade of the 20th century: Z. Žemaitis’s “Differential-integral calculation”: „Diferencialinis-integralinis skaičiavimas“ - Banionis, Juozas (Lietuvos matematikos rinkinys, 2018)
Zigmas Žemaitis (1884–1969) is the professor who is called the patriarch of Lithuania’s mathematicians, the one who led foundation of science of the Republic of Lithuania of the 16th of February. Z. Žemaitis’s merit is significant in publishing the first textbooks of high mathematics in Lithuanian. The article is aimed at discussing the conditions under which quite forgotten Z. Žemaitis’s textbook “Differential-Integral Calculation” came to existence and its content. The article also considers the importance of the textbook for increasing the role of teaching differential-integral calculations in higher educational institutions in Lithuania.
Keywords: mathematical employment